183k views
2 votes
Simplify the algebraic expression by combining like terms.

Expression
Expression by Combing Like Terms
4x + 2y - 3x + 2 + 5y

User Fanhats
by
4.8k points

2 Answers

4 votes
Combine the x together and combine the y together
So 4x-3x=x, 2y+5y=7y
So the answer will be x+7y+2
User Show
by
4.4k points
3 votes

Answer:

x + 7y + 2

Explanation:

here's your solution

=> Given expression is

=> 4x + 2y - 3x + 2 + 5y

=> now, putting together like term

=> 4x - 3x + 2y + 5y + 2

=> now, solve for like term

=> x + 7y + 2

hope it helps

User Avalanchy
by
4.3k points